Determinants of The Firm Value in Indonesia - Marshelino Boyke Kristanto; Lodovicus Lasdi (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2021)
Companies are no longer only faced with a single bottom line that centers on financial conditions, but companies must adjust to the triple bottom line concept. One form of environmental responsibility for corporate management for stakeholders and shareholders is by disclosing greenhouse gas emissions. Company value is also a very important factor because it can describe the business processes in a company. A high company value will provide a strong interest for investors to buy shares. An increase in stock prices will also increase the value of a company. This study aims to test and obtain empirical evidence regarding the effect of greenhouse gas disclosure, profitability and leverage on firm value. The population of this research is mining sector companies listed on the Indonesia Stock Exchange during the 2014-2018 period. The sample selection in the study using purposive sampling method. The data analysis technique used multiple linear regression. The results of this study indicate that the variable of greenhouse gas disclosure and profitability has a significant positive effect on firm value. The leverage variable does not have a significant effect on firm value, this is because the amount of debt held by the company is not a major concern for investors because investors are more concerned with how management uses the debt effectively and efficiently for use in developing the company